Nonlinear Approximation by $q$-Favard-Szász-Mirakjan Operators of Max-Product Kind - Ecem Acar; Döne Karahan (Communications in Advanced Mathematical Sciences, 2023)
In this study, nonlinear $q$-Favard-Szász-Mirakjan operators of max-product kind are defined and approximation properties of these operators are investigated. Classical approximation and $A$-statistical approximation theorems are given.